COLLABORATIVE GOVERNANCE DALAM PELAKSANAAN PROGRAM URBAN FARMING DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Haerul Haerul (Jurnal Aktor, 2026)
This study aims to analyze the concept of Collaborative Governance in the implementation of the Urban Farming Program in Rappocini District, Makassar City, based on the theoretical perspective of Ansell and Gash (2008). This study employed a literature review method with a descriptive qualitative approach. Data were obtained from various secondary sources, such as scientific journals, books, research reports, and policy documents relevant to the themes of Collaborative Governance and urban farming. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing based on the model of Miles, Huberman, and Saldaña (2014). The results show that the implementation of the Urban Farming Program in Rappocini District is influenced by four main dimensions of Collaborative Governance, namely starting conditions, institutional design, facilitative leadership, and collaborative process. In the starting conditions dimension, collaboration emerged due to limited urban land, the need for food security, and interdependence among actors. In the institutional design dimension, the involvement of government, communities, academics, community groups, and the private sector indicates the existence of an institutional structure that supports participation. Furthermore, in the facilitative leadership dimension, the government plays a role as a facilitator in building communication and coordination among stakeholders. Meanwhile, in the collaborative process dimension, collaboration is characterized by face-to-face dialogue, trust building, commitment, shared understanding, and intermediate outcomes that encourage increased community participation and the utilization of urban land. The conclusion of this study indicates that Collaborative Governance is a relevant and effective approach to explain the implementation of the Urban Farming Program in Rappocini District, Makassar City. The success of the program is highly determined by the synergy among stakeholders in building sustainable, participatory, and goal-oriented cooperation, particularly toward food security and the empowerment of urban communities.